Linear mathematics - The Open University BBC TV; Vivienne King ([United Kingdom] : The Open University, 1971)
Review tutorial of algebra includes linear equations, factoring, inequalities.
Converted into VHS 1/2 in. and DVD
filem 20 AS122.06.M201
Graphic design, Beverley Clarke.
Narrator : Ian Hey.
Keywords: Algebras, Linear; Mathematics